Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0921
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and insect toxicity of propylene oxide in dried fruits and nuts.

Abstract: Dried fruits and nuts were fumigated with a mixture of propylene oxide (PPO) and CO2 (8%:92% w/w) in 28.42-litre chambers to determine PPO sorption rates in these products and toxicity to a variety of postharvest insect pests. A 48-h fumigation using a rate of 45 mg/litre at 38°C resulted in more than 97% sorption in almonds, pecans and walnuts, and induced 100% mortality of mixed life stages of the following insects: Indian meal moth (Plodia interpunctella), red flour beetle (Tribolium castaneum), confused fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although we did not quantitatively measure PPO or EF sorption or residues in the fish meal, ham, or pet food studies, our results show that different commodities can have different sorption qualities, which can impact pest mortality. Earlier work showed PPO to have high sorption rates in several commodities [ 20 , 23 , 37 ]. EF has also been reported to have sorption properties in wheat [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not quantitatively measure PPO or EF sorption or residues in the fish meal, ham, or pet food studies, our results show that different commodities can have different sorption qualities, which can impact pest mortality. Earlier work showed PPO to have high sorption rates in several commodities [ 20 , 23 , 37 ]. EF has also been reported to have sorption properties in wheat [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term “sorption” in fumigation refers to a decrease in gas concentration not resulting from a leak in the structure being fumigated. The desorption of a fumigant refers to the release of a fumigant from a certain commodity at some time after the ventilation of the structure or chamber that was fumigated [ 20 ]. The qualitative detection of the sorption and desorption of EF or PPO related to the commodity was determined with a variation in the mortality of T. putrescentiae caused by the presence of a commodity in the fumigation chamber compared to the mortality of the mites’ empty chamber which was fumigated in the same way but with no commodity.…”
Section: Methodsmentioning
confidence: 99%
“…A range of treatments are being investigated as possible substitutes of MBr for pest control in the dried fig industry. In particular, these alternative fumigants have been tested: phosphine (PH), released by the hydrolysis of magnesium phosphide (Meyvaci et al, 2003b;Aksoy et al, 2008;Meyvaci et al, 2009); sulfuryl fluoride ; propylene oxide in combination with CO 2 (Zettler et al, 2003); CO 2 (Ferizli and Emekci, 2000;Emekçi et al, 2003;Meyvaci et al, 2003bMeyvaci et al, , 2009); CAs comprising ≤1% O 2 ; and 10-15% CO 2 (Damarli et al, 1998;Navarro et al, 1998).…”
Section: Pestsmentioning
confidence: 99%
“…The effectiveness of COS as an agricultural fumigant is proportionate to both exposure time and applied concentration. Thus, lower concentrations are equally effective as long as the exposure period is longer. , Another advantage of carbonyl sulfide is its much lower combustibility when compared to other fumigants such as phosphine.…”
Section: Recent Application:  Cos As An Agricultural Fumigantmentioning
confidence: 99%
“…Zettler has shown that a 24-h exposure of several insect species to carbonyl sulfide at the concentration of 25 mg/L led to their complete extermination. The successful results were, in order of susceptibility, the larval navel orangeworm, Amyelois transitella (Walker); the adult sawtooth grain beetle, Oryzaephilus surinamensis (L.); the adult dried fruit beetle, Carpophilus hemipterus (L.); the adult cigarette beetle, Lasioderma serricorne (F.); and the adult confused flour beetle, Tribolium confusum (Jaquelin DuVal). , Plare and Reichmuth 246,247 found that a concentration of 32 mg/L for 72 h successfully controlled the granary weevil ( Sitophilus granarius ). Similarly, 99.8% of the rice weevil and the lesser grain borer ( Rhyzopetha dominica ) was killed upon a 24-h exposure at 25 mg/L, and 98.1% of the same insect was destroyed upon a 72-h exposure at 8 mg/L.…”
Section: Recent Application:  Cos As An Agricultural Fumigantmentioning
confidence: 99%